2009
DOI: 10.1002/cncr.24200
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 mutations in women of different ethnicities undergoing testing for hereditary breast‐ovarian cancer

Abstract: BACKGROUND:In women at increased risk for breast and ovarian cancer, the identification of a mutation in breast cancer gene 1 (BRCA1) and BRCA2 has important implications for screening and prevention counseling. Uncertainty regarding the role of BRCA1 and BRCA2 testing in high‐risk women from diverse ancestral backgrounds exists because of variability in prevalence estimates of deleterious (disease‐associated) mutations in non‐white populations. In this study, the authors examined the prevalence of BRCA1 and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
304
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(332 citation statements)
references
References 49 publications
20
304
2
3
Order By: Relevance
“…To date, studies of BRCA1 mutation spectrum in Chinese populations are limited and most of these studies were performed in single institutions or a small number of medical centers .The mutation rates of BRCA1 in familial breast cancer ranged from 3.9% to 6.9% ( Cao et al, 2013). This is consistent with rates in other Asian ethnic groups (Hall et al, 2009). Another study, by Suter et al (2004) found that the rates of BRCA1 mutations in sporadic breast cancers were 0.7% (4/590) in Shanghai of China.…”
Section: Brca1 Gene Exon 11 Mutations In Uighur Andsupporting
confidence: 64%
“…To date, studies of BRCA1 mutation spectrum in Chinese populations are limited and most of these studies were performed in single institutions or a small number of medical centers .The mutation rates of BRCA1 in familial breast cancer ranged from 3.9% to 6.9% ( Cao et al, 2013). This is consistent with rates in other Asian ethnic groups (Hall et al, 2009). Another study, by Suter et al (2004) found that the rates of BRCA1 mutations in sporadic breast cancers were 0.7% (4/590) in Shanghai of China.…”
Section: Brca1 Gene Exon 11 Mutations In Uighur Andsupporting
confidence: 64%
“…Mutation BRCA1 185delAG was the most prevalent, observed in 7 (54%) of the 13 mutation carriers, and is the most common founder mutation in the Ashkenazi Jewish population. It has also been reported in other population groups living in Mexico, Chile, and the Bahamas [19,29,30]. The frequency observed in Peru (54%) is the highest yet reported in nonselected populations in Latin America.…”
Section: Perumentioning
confidence: 63%
“…The prevalence of mutations in BRCA1/2 is different in various ethnic groups and may be affected by founder mutations 5) . Earlier studies of BRCA1/2 mutations were largely based on Caucasian.…”
Section: Prevalence Of Brca1/2 Germline Mutations In Chinese Women Wimentioning
confidence: 99%
“…Earlier studies of BRCA1/2 mutations were largely based on Caucasian. It has been reported that BRCA1/2 mutations account for 15-20% of familial cases in Caucasian populations 5) . Recently, a number of studies have focused on the Chinese population.…”
Section: Prevalence Of Brca1/2 Germline Mutations In Chinese Women Wimentioning
confidence: 99%